Advocacy and the search for truth in management scholarship: can the twain ever meet? - Wright, Thomas A.; Emich, Kyle; Pearce, Jone L.; Denyer, David (Sage, 2024)
Scholars have long debated the merits of advocacy-based research versus research considered from the quest for objective truth. Building upon reflections from multiple sources, a set of 11 brief reflections on three posed questions are presented. Tsang concludes our discussion with additional insights on how moving beyond the “interestingness” advocacy will be beneficial to the continued professional development of the management discipline.
Keywords: academic freedom; advocacy; interestingness; kindness; scientific discourse; truth